Divergent Barmah Forest Virus from Papua New Guinea - Leon Caly; Paul F. Horwood; Dhanasekaran Vijaykrishna; Stacey Lynch; Andrew R. Greenhill; William Pomat; Glennis Rai; Debbie Kisa; Grace Bande; Julian Druce; Mohammad Y. Abdad (Emerging Infectious Diseases, 2019)
We report a case of Barmah Forest virus infection in a child from Central Province, Papua New Guinea, who had no previous travel history. Genomic characterization of the virus showed divergent origin compared with viruses previously detected, supporting the hypothesis that the range of Barmah Forest virus extends beyond Australia.